AIAA Infotech@Aerospace Conference 2009
DOI: 10.2514/6.2009-1930
|View full text |Cite
|
Sign up to set email alerts
|

System Identification of Post Stall Aerodynamics for UAV Perching

Abstract: For a UAV to perch on a wire, aircraft control systems which operate far outside typical operating envelopes must be developed. The relevant transient aerodynamics at high angle of attack are not addressed today by control-accessible aerodynamic models. In this work, we present a set of physically-inspired basis functions which have enabled system identification of a nonlinear aerodynamics model along perching trajectories. Data is collected using a motion capture system which, critically, allows free-flight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…In [11], [17], it was shown that this method is capable of accurately predicting the aerodynamics of UAV perching under unsteady flight regimes.…”
Section: Flight Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [11], [17], it was shown that this method is capable of accurately predicting the aerodynamics of UAV perching under unsteady flight regimes.…”
Section: Flight Dynamicsmentioning
confidence: 99%
“…It is straightforward to obtain an analytic solution to equation (11). Though, for the sake of simplicity and tractability, here we opt to replace the integration with a finite sum by dividing the damper into two pieces, separated by theẑ-axis.…”
Section: A Damper Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, promising results have been documented, regarding dynamics model identification for non-routine flight conditions or envelopes. Two successful cases can be founded in reports [40,44], in which system identification is applied to model take-off process (based on ARX/ ARMAX/BJ models) and perching (based on decoupled 6-DoF rigid-body dynamics model).…”
Section: Dynamics Modeling Of Small-scale Fixed-wing Uavsmentioning
confidence: 99%